Fabrication of Oxygen Vacancy-Rich WO3 Porous Thin Film by Sputter Deposition for Ultrasensitive Mustard-Gas Simulants Sensor - Li, Haizhen; Yan, Cancan; Shen, Jun; Liu, Shuai; Ma, Qingyu; Zheng, Yongchao (Sensors (Basel, Switzerland), 2025)
Exposure to sulfur mustard can result in severe injury or even fatalities in humans. Therefore, the development of reliable and high-performance sensors for detecting sulfur mustard is critical. Herein, WO3 thin films are prepared as sulfur mustard simulant (e.g., 2-chloroethyl ethylsulfide, 2-CEES) sensing materials using sputter deposition followed by high-temperature annealing. The 2-CEES gas sensors fabricated via WO3 porous films realize high-performance detection of 2-CEES at 260 °C with an impressive detection limit (15 ppb), fast response (58 s), long-term stability, and good selectivity. Through systematic optimization of deposition and annealing parameters, WO3 porous thin films with tailored oxygen vacancy concentrations were prepared, facilitating device fabrication. This approach provides an effective strategy for the batch production of miniaturized devices enabling real-time monitoring of vesicant agents.